Hemorragia pulmonar em prematuros de extremo baixo peso : fatores de risco e tratamento - Iepsen, Juliane (2014)
OBJECTIVES : To assess the association between fluid management and the occurrence of pulmonary hemorrhage in extremely low birth weight infants. To investigate prenatal conditions (as corticosteroid and intrauterine growth restriction) and postnatal conditions (as surfactant and patent ductus arteriosus) as possible risk factors for pulmonary hemorrhage in premature infants. PATIENTS AND METHODS : A retrospective case-control study was conducted through analysis of medical records, in the Neonatal Intensive Care Unit of Hospital São Lucas da PUCRS, Porto Alegre, Brazil, including the period between 2003 and 2013. All infants with birth weight less than or equal to 1000 g who developed a clinical picture of massive pulmonary hemorrhage were eligible for the study. Infants without pulmonary hemorrhage, at the same range of weight and/or gestational age, born consecutively to each case, were selected as controls. RESULTS : Fifty-six preterm infants, 28 cases and 28 controls, participated in the study. Patients with pulmonary hemorrhage had higher in-hospital mortality, occurring 23 deaths (82.1%), when compared with controls, who had 12 deaths (42.9%) (p=0.006). Intracranial hemorrhage was diagnosed in 12 of 28 cases (48%) and in four of 28 control patients (14%) (p=0.01). Diuresis in the second day of life was lower in the pulmonary hemorrhage group (2.5 mL/kg/h) compared with controls (3.5 mL/kg/h) (p=0.019). In the group of cases, reduction of the infused volume was associated with the outcome: of the 21 patients who had fluid restriction, 15 (71.5%) survived to pulmonary hemorrhage, whereas all patients in whom the reduction in volume was not performed had pulmonary hemorrhage-related death (p=0.003). Volume reduction associated with the use of diuretic was also associated with lower risk of death from pulmonary hemorrhage: in 14.2% of those who used this combination and 69.2% of those who did not use, death due to pulmonary hemorrhage occurred (p=0.006). These results suggest that fluid retention may be associated to the occurrence of pulmonary hemorrhage and that the management with infused volume restriction and diuretic administration shortly after the start of pulmonary hemorrhage can be effective in reducing mortality.